EFFICIENCY STUDY IN A HYGIENIZATION SYSTEM IN THE COCONUT WATER BOTTLE INDUSTRY - Figueredo, Odair Mascarenhas; Rodolpho, Daniela (Revista Interface Tecnológica, 2023)
The CIP (Cleaning in Place) sanitation process is essential to ensure the safety, maintenance of organoleptic characteristics, and quality of coconut water to be bottled. In this article, I present the theoretical basis of CIP sanitation in the coconut water bottling industry, as well as the methodological procedures to assess the effectiveness of the cleaning process. Results and discussion indicate that appropriate selection of alkaline, acidic, and sanitizing cleaning solutions, establishment and implementation of cleaning protocols, validation of the cleaning process by the quality control department, training of employees involved in the entire process, and documentation of the process are critical to ensure the effectiveness of CIP sanitation. Finally, I highlight the importance of companies investing in continuous improvements in the CIP sanitation process to ensure product quality and safety.